Analisis Kunjungan Pengunjung dari Perspektif Motivasi dan Persepsi Atraksi Heritage pada Kawasan Kota Tua Jakarta - Isti Andira Rachmadiyah Latief; Fauziah Eddyono (Universitas Batanghari, 2023)
The perspective of motivation and perception of heritage is the main driving force and attraction for visitors to make a visit to the Kota Tua Jakarta area. This study aims to determine the influence of visitor motivation and perceptions of heritage attractions on the decision to visit and impact on the decision to return to the Kota Tua area of Jakarta. Researchers also formulate a priority strategy for performance improvement in the Kota Tua Jakarta area through visitor motivation and perceptions. This research is quantitative descriptive. Data analysis used a path test with the SEM Model and AMOS 26.0 Program assistance. Meanwhile, the priority strategy uses Multidimensional Scaling and Importance-Performance Analysis (IPA) diagrams. The results of the study show that: (1) Push factor motivation has no effect on the decision to visit the Kota Tua Jakarta area, (2) Push factor motivation has a significant influence on the decision to visit the Kota Tua Jakarta area with a CR value of 1.969 and p of 0.049 and a contribution of 20.8%, (3) Heritage attractions do not have an influence on the decision to visit the Kota Tua Jakarta area, (4) The decision to visit has a significant influence on the decision to visit again to the Kota Tua Jakarta area with a CR value of 2.181 and p of 0.029 as well as a contribution of 22.9% and (5) Priority strategies that must be developed in improving the Kota Tua Jakarta area are in the attributes of heritage attractions, namely Shopping, Aesthetics, Congeniality, Scarcity, Influence, and History.